IMPLEMENTASI PELAYANAN PERIZINAN TERPADU SATU PINTU - Yuli Tirtariandi El Anshori; Enceng '; Anto Hidayat (JIANA ( Jurnal Ilmu Administrasi Negara ), 2014)
The Implementation of Integrated Licensing Services. The purpose of the study is tofind an overview of the implementation of OSS, especially in Bangka Regency. The researchuses qualitative descriptive method. Then, The primary data are obtained from interviews andobservations, and the secondary data are obtained from the documents. The analysis of the datausing triangulation method. The results show that the commitment of the Bangka Regency headin implementing OSS is good, but the problem is found in terms of the functions of coordination.It arises as the impact of institutional forms. The impact of the pull of interests between thetwo institutions in the public service licensing can result in low confidence of the businessmenbureaucratic public service providers.Keywords: implementation, integrated public services, coordination